Beyond Efficiency: Exploring Employee Experiences of Process Innovation in Service Sector Operations - Syahrul Anwar (Politeknik Siber Cerdika Internasional, 2025)
implement process innovations to enhance operational efficiency and competitiveness. H In today’s rapidly evolving service industry, organizations increasingly implement process innovations to enhance operational efficiency and competitiveness. However, existing literature has primarily focused on efficiency metrics, often overlooking the experiential dimensions of such innovations from the employee perspective. This research aims to explore how employees perceive, experience, and respond to process innovation initiatives within service sector operations. Using a mixed-methods approach, the study collected data from 185 employees across various service-based organizations through structured surveys and in-depth interviews. Quantitative data were analyzed using SPSS 26.0 and NVivo 12 was used for thematic analysis of qualitative inputs. The findings reveal that while process innovations often result in measurable improvements in workflow efficiency, their implementation also impacts employee engagement, job satisfaction, and perceived autonomy. Specifically, employee involvement in the innovation process significantly enhances creative self-efficacy and fosters proactive behavior. The study contributes to service innovation literature by emphasizing the role of human-centered perspectives in process redesign. It also highlights the need for managerial strategies that strike a balance between technical efficiency and the emotional and motivational needs of employees. Practically, the findings suggest that inclusive and participatory innovation practices not only improve operational outcomes but also support sustainable workforce development. Future research is encouraged to explore longitudinal effects of process innovation and test models across different cultural or organizational contexts. owever, existing literature has primarily focused on efficiency metrics, often overlooking the experiential dimensions of such innovations from the employee perspective. This research aims to explore how employees perceive, experience, and respond to process innovation initiatives within service sector operations. Using a mixed-methods approach, the study collected data from 185 employees across various service-based organizations through structured surveys and in-depth interviews. Quantitative data were analyzed using SPSS 26.0 and NVivo 12 was used for thematic analysis of qualitative inputs. The findings reveal that while process innovations often result in measurable improvements in workflow efficiency, their implementation also impacts employee engagement, job satisfaction, and perceived autonomy. Specifically, employee involvement in the innovation process significantly enhances creative self-efficacy and fosters proactive behavior. The study contributes to service innovation literature by emphasizing the role of human-centered perspectives in process redesign. It also highlights the need for managerial strategies that strike a balance between technical efficiency and the emotional and motivational needs of employees. Practically, the findings suggest that inclusive and participatory innovation practices not only improve operational outcomes but also support sustainable workforce development. Future research is encouraged to explore longitudinal effects of process innovation and test models across different cultural or organizational contexts.